DETERIORATION OF BLEACHABILITY INDEX DAN STABILITAS MINYAK SAWIT MENTAH YANG BERASAL DARI TINGKAT KEMATANGAN YANG BERBEDA - Ika Ucha P.Rangkuti; Heri Purwanto (Institut Teknologi Sawit Indonesia (ITSI), 2020)
Deterioration of bleachability index (DOBI) reflects the paleness index of crude palm oil which has the aim ofremoving the color (bleaching) that is less favored in oil, so DOBI is quite important to assist processing inrefining palm oil. This study aims to determine the DOBI value contained in crude palm oil derived fromdifferent levels of fruit maturity namely unripped fruit, riped and overripe on oil palm at 850 meters above sealevel, as well as its stability on heating for 0 and 24 hours. The results showed that ripe fruit has a DOBIvalue of 1.75 and has better stability compared to raw fruit and through ripe.